Breeding Technology as a Tool for Sustainable Aquaculture Production and Ecosystem Services - Azra, Mohamad Nor; Okomoda, Victor Tosin; Ikhwanuddin, Mhd (Frontiers in Marine Science, 2022)
Aquaculture is the aquatic equivalent of agriculture. While agriculture is predominantly based on the use of freshwater to grow crops, aquaculture utilizes freshwater (i.e. inland waters) and brackish water / seawater (i.e. coastal waters) to culture fish, plants, shellfish (bivalve, abalone, sea urchins and sea cucumbers), macro and microalgae. The increasing scarcity of captive aquatic fisheries resources has led to the regenerative farming practices of aquaculture. Aquaculture is the fastest-growing food sector in the world and about the most important means of providing sustainable food production currently. Among the several aquaculture techniques used, breeding technology has been exploited to improve food production. Beyond captive production, breeding technology has also been exploited for restocking programs of many aquatic ecosystems (i.e. rivers, lakes, sea, estuaries, etc.), hence, contributing positively to their management and ecosystem services. This comment, therefore, highlights some breeding technology as regards to their ability to improve sustainable captive production and aquatic ecosystem services.